Crane scheduling problem with non-interference constraints in a steel coil distribution centre. Issue 6 (19th March 2017) - Maschietto, Gabriela N.; Ouazene, Yassine; Ravetti, Martín G.; de Souza, Maurício C.; Yalaoui, Farouk
Abstract : This article deals with a parallel machine scheduling problem subject to non-interference constraints. This situation often appears at logistic centres, such as depots, warehouses and stockyards. The analyzed scenario is based on a real case at a distribution centre of steel coils, where two cranes using the same rail must load dispatching trucks. We analyze this case by modelling the situation through a parallel machine perspective and considering two mechanisms to deal with the machine interference, . In the first approach, the machine interference is dealt by scheduling whole trucks. In the second one, we schedule the trucks and the coils within. The proposed mathematical models are able to solve small and medium instances, thus, we develop two genetic algorithms to solve real size instances, allowing the analysis of different storage policies. Results show that the genetic approach is able to find near-optimal solutions independently of the policy, with solutions gap ranging from 10 to 2.1%.